Packaging design for competitiveness. Contextualizing the search and adoption of changes from a sustainable supply chain perspective - Jesus García-Arca; A. Trinidad González-Portela Garrido; J. Carlos Prado-Prado; Iván González-Boubeta (International Journal of Production Management and Engineering)
The “Sustainable Packaging Logistics” (SPL) approach seeks sustainable integration of the combined “packaging-product-supply chain” system orientated to increase competitiveness. However, characterizing which changes make it possible to guide such design in each company and supply chain is an aspect that has not been covered in the literature from different supply chain perspectives. The main goal of this paper is to identify and justify the main actions for improvement in SPL, combined with a proposal of methodology for contextualizing, selecting and implementing each of these potential actions, applying the “Action Research” approach. Likewise, this paper illustrates the interest of this methodology with its adoption in four different companies and supply chains. This paper opens up new avenues of applied research in packaging design, generating knowledge that contributes to sustainable and competitive improvement.